Rolling stand electric drive model regarding influence of power supply network parameters - Druzhinin Valery Mikhailovich; Kalinin Alexey Anatolievich; Sivyakova Galina Alexandrovna (Institute of Advanced Engineering and Science, 2023)
Operation mode of hot rolling mill finishing group stands of ArcelorMittal Temirtau JSC electric drives along with thyristor converter units, intended for the drives supply effect significantly the power network parameters. While being carried out the experimental research on operating modes of power network supplying the rolling mill, some oscillograms were constructed that indicate voltage during the rolling process. Analyzing the oscillograms it appears that there are unacceptable voltage drops throughout the network (more than 10%), that, in its turn, effects negatively the main and auxiliary electric drives functioning. Electric drive simulation model have been constructed with the aim accomplishment to learn more about operating modes features of finishing group stands electric drives as well as power network supplying the hot rolling mill, where the main objective is getting the decreased parameters of their mutual influence. The scientific project purpose is verification of the mathematical model choice correctness, construction of a simulation model of the electric drive control system for the main drives of the hot rolling mill stands, taking into consideration the parameters of the power supply network and checking its adequacy.